Training Of Village Health Cadres On Prevention Of Anaemia Among Pregnant Women In Bojonegoro District - ernawati, masfuah; Indrayanti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Anaemia in pregnancy is a condition of the mother with haemoglobin levels below 11gr% in the 1st and 3rd trimesters or levels <10.5gr% in the 2nd trimester. The incidence of anaemia in pregnant women in Mojodeso Village, Kapas District, Bojonegoro in 2020 was 6 out of 30 pregnant women or 20%. higher than the incidence of anaemia in pregnant women in the Kapas Puskesmas work area 6.20%. The purpose of this community service is to increase the knowledge and skills of Village Health Cadres on Prevention of Anaemia in Pregnant Women in Mojodeso Village, Kapas District, Bojonegoro Regency. The methods used in empowerment activities in the form of Village Health Cadre Training on Prevention of Anaemia in Pregnant Women are lectures, questions and answers, demonstrations, extension practices, pre tests and post tests. The training was held for 3 (three) days on 21, 22 and 23 June 2022 at the Mojodeso Village Hall, Kapas District, Bojonegoro Regency with 30 health cadres participating. The results of this training were that there was an increase in the lowest, highest, and average knowledge scores of the trainees with the most 26 (86.73%) post test scores in the very good category. The average value of IEC practice of most trainees is very good category as many as 21 participants (70%) very good category. All trainees provided counseling to 30 (100%) participants, each of whom provided counseling to 5 couples of childbearing age, resulting in a total of 150 couples of childbearing age who received counseling on the prevention of anaemia in pregnant women. Pregnant women can prevent anaemia by consuming foods that contain blood supplements and processing them properly